\[\boxed{\text{586\ (586).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ (x - 12)(x + 12) =\]
\[= 2 \cdot (x - 6)^{2} - x^{2}\]
\[x^{2} - 144 =\]
\[= 2 \cdot \left( x^{2} - 12x + 36 \right) - x^{2}\]
\[x^{2} - 144 =\]
\[= 2x^{2} - 24x + 72 - x^{2}\]
\[24x = 216\]
\[x = 9\]
\[Ответ:x = 9.\]
\[2)\ (3x - 1)^{2} + (4x + 2)^{2} =\]
\[= (5x - 1)(5x + 1)\]
\[10x = - 6\]
\[x = - 0,6\]
\[Ответ:\ x = - 0,6.\]
\[16x = - 80\]
\[x = - 5\]
\[Ответ:\ x = - 5.\]
\[\boxed{\text{586.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 3(m + n) + x(m + n) =\]
\[= (m + n)(3 + x)\]
\[2)\ 8(c - 1) - a(c - 1) =\]
\[= (c - 1)(8 - a)\]
\[3)\ 4b(a + 2) + 3(a + 2) =\]
\[= (a + 2)(4b + 3)\]
\[4)\ ab(a - c) + 2c(c - a) =\]
\[= (a - c)(ab - 2c)\]